The development of key national policies with respect to rainwater management in Ethiopia: A review - Ethiopian Economics Association (International Livestock Research Institute, 2011)
Several national economic and sectoral policies and strategies were developed, adopted and being implemented over the last couple of decades in Ethiopia. These policies and strategies provide frameworks and guides for economic management in a wide range of aspects. There are policies that support and lay a good ground for the development and implementation of RWM interventions. These policies are general like the ones that affect the agricultural sectoral development and specific ones that are important for water sector, environment and natural resources. Five major challenges are quite often mentioned with respect to policy implementation. These are the fact that policies are made without adequate assessment and drawing lessons of existing/old policies (strategies); lack or absence of policy implementation guidelines, laws and regulations; a general lack of policy implementation capacity at all levels; a general lack of proper policy implementation, monitoring and evaluation system that could feed into policy refinement and adjustment; and the challenge of policy coordination and integration (across sectors).